2018
DOI: 10.4103/jcd.jcd_373_16
|View full text |Cite
|
Sign up to set email alerts
|

A scanning electron microscope evaluation of efficacy of sodium hypochlorite and Allium sativum in smear layer removal in root canals with the use of modified evacuation system: An ex vivo study

Abstract: Context:Sodium hypochlorite (NaOCl) is the most widely used endodontic irrigant. Although it fulfills most of the requisites of an ideal irrigant, it has certain drawbacks, chiefly severe soft-tissue damage. Allium sativum (garlic extract) is a proven antimicrobial agent that has the ability to dissolve inorganic tissue with minimal toxicity. However, its ability to remove smear layer (SL) is not known. Conventional hand-held syringe irrigation is ineffective in removing canal debris. The use of newer irrigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In recent ex vivo study the efficacy of sodium hypochlorite (NaOCl) and garlic in smear layer removal in root canals is examined. They observed the elimination of irrigant as well as debris from root canals in 68 single-rooted mandibular premolars treated with 5% NaOCl and 17% ethylenediaminetetraacetic acid (EDTA) with GE (64 mg/mL) prepared by garlic cloves in 70% ( v / v ) ethanol [ 105 ].…”
Section: Oral Pathologies and Beneficial Role Of Ge In The Alleviationmentioning
confidence: 99%
“…In recent ex vivo study the efficacy of sodium hypochlorite (NaOCl) and garlic in smear layer removal in root canals is examined. They observed the elimination of irrigant as well as debris from root canals in 68 single-rooted mandibular premolars treated with 5% NaOCl and 17% ethylenediaminetetraacetic acid (EDTA) with GE (64 mg/mL) prepared by garlic cloves in 70% ( v / v ) ethanol [ 105 ].…”
Section: Oral Pathologies and Beneficial Role Of Ge In The Alleviationmentioning
confidence: 99%
“…The extract exhibits a wide range of inhibitory effect on the growth of various bacteria due to the presence of thiosulfinates which include diallyl sulfide, diallyl disulfide, and allyl methyl sulfide, which disrupt the cell membrane of the bacteria and block their enzymatic pathways. [ 12 13 15 16 ] The results of the current study showed statistically significant activity against both aerobic and anaerobic bacterial growth ( P < 0.01). Up to the available data, the use of AS extract in endodontic treatment is limited.…”
Section: Discussionmentioning
confidence: 67%
“…Using a sterile mortar and pestle, cloves were homogenized aseptically and filtered through a double layer paper. The fully concentrated and extracted was diluted to the concentration of 25% with distilled water (Eswar, Venkateshbabu, Rajeswari, & Kandaswamy, 2013;Prabhakaran & Mariswamy, 2018).…”
Section: A Sativum Extract Preparationmentioning
confidence: 99%
“…The complex nature of the deciduous root canal system facilitates the spread of pathogenic microbes through lateral and accessory canals, dentinal tubules, apical ramifications, and the possibility of harming the tooth germ of permanent successor, and subsequently, these barriers make total removal of necrotic tissue by instrumentation alone impossible (Camp, 2008;Pazelli et al, 2003;Pozos-Guillen, Garcia-Flores, Esparza-Villalpando, & Garrocho-Rangel, 2016;Vianna et al, 2004). Therefore, irrigation is a replenishing step to mechanical instrumentation during root canal preparation to create a disinfectant atmosphere inside the root canal (Prabhakaran & Mariswamy, 2018). Another critical function of intracanal irrigation is elimination of the smear layer that raises dentin permeability and allows permeation of intracanal medication (Pashley, Michelich, & Kehl, 1981;Teixeira, Felippe, & Felippe, 2005;Zehnder, 2006).…”
Section: Introductionmentioning
confidence: 99%